-(5y+5)-(-4y-7)=-1

Simple and best practice solution for -(5y+5)-(-4y-7)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5y+5)-(-4y-7)=-1 equation:


Simplifying
-1(5y + 5) + -1(-4y + -7) = -1

Reorder the terms:
-1(5 + 5y) + -1(-4y + -7) = -1
(5 * -1 + 5y * -1) + -1(-4y + -7) = -1
(-5 + -5y) + -1(-4y + -7) = -1

Reorder the terms:
-5 + -5y + -1(-7 + -4y) = -1
-5 + -5y + (-7 * -1 + -4y * -1) = -1
-5 + -5y + (7 + 4y) = -1

Reorder the terms:
-5 + 7 + -5y + 4y = -1

Combine like terms: -5 + 7 = 2
2 + -5y + 4y = -1

Combine like terms: -5y + 4y = -1y
2 + -1y = -1

Solving
2 + -1y = -1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -1y = -1 + -2

Combine like terms: 2 + -2 = 0
0 + -1y = -1 + -2
-1y = -1 + -2

Combine like terms: -1 + -2 = -3
-1y = -3

Divide each side by '-1'.
y = 3

Simplifying
y = 3

See similar equations:

| 4(3x-7)-5(4x-2)= | | 7x+7=9x-9 | | 23x+67=55x-40 | | x^2+4x+6=10 | | 54*4= | | x+57,x=3 | | 4.39(5)+3.42N=76.11 | | 8x+2=7(x-4)+8 | | 6-5y=7-6y | | 2x+4=-7(-7x+6) | | 8y+2=7y-4 | | .6u-7=9-.6u | | 5-5x+8+2x+4x-2=6+4*3 | | 1.12a=149000000 | | 7g+5=12g-25 | | 6p-(5p-5)=-8-2(p+12) | | 3x^4(7x^3-4x-1)= | | .25+9=10-.75r | | 5x(1-x)=5(x-2) | | 6x^2-7x-20=(2x-5)(3x+4) | | x(2x-3)=35 | | z^4+2z^2-4z=0 | | 8+4x-12-2x=8 | | (8a-7)(4a-3)=0 | | 3x^2+4x-5-7x^2-4x+8= | | 12(3x-9)=3(12x+5) | | In(x)=7 | | 42=6t | | 2x-8=x+7 | | Ln(4x-5)=0 | | 157.78=2.41w+14.23 | | -421=7(-4+7n)-1 |

Equations solver categories